PELATIHAN ANDROID UNTUK SISWA / SISWI SMK NASIONAL MALANG - As'ad, Mohamad; Farida, Eni; Sami, Sri Esti Trisno (Jurnal Terapan Abdimas, 2020)
Abstract. Android training for students of Malang National Vocational School is one form of social service which is one of the elements of the tri darma perguruan tinggi and must be implemented by the academic community. This training was conducted at the STMIK PPKIA Pradnya Paramita (STIMATA) campus in Malang. This training was conducted after STIMATA lecturers received the same training from Google in the form of the "Indonesia Android Kejar (IAK)" program. This training is a form of a study group that is collaborated with society service for STIMATA lecturers. The purpose of this training is to provide knowledge and insight for the community, especially the students of the National Vocational School of Malang about android. This training is also to improve the skills for students of Malang National Vocational School to create an Android-based application. This training is held for two days, Monday-Tuesday January 29-30 2018 at the STMIK PPKIA Pradnya Paramita Malang Computer Laboratory from 08.00 W1B to 16.00 WIB. This training was attended by 29 students of the National Vocational School of Malang. This training uses two applications, namely android studio which is installed on a computer PC to make the program and java program to compile when the participants want to be placed on an Android mobile. The training was given the material in a row view, group views, creating projects, interactive applications, screening and calling methods and the last objected-oriented program. After all training materials are given, the participants are given the task of making a simple application project that can be run on their respective Android phones. To provide an ability assessment, it is assigned to make a project that is more complex and given a month which is then sent to the tutor's e-mail. The final results of the training turned out that all participants were able to receive the material well and were able to spell out the assignment as a substitute for the exam well. Thus this training can run as expected. Abstrak. Pelatihan android bagi siswa-siwa SMK Nasional Malang merupakan salah satu bentuk pengabdian masyarakat yang merupakan salah satu unsur tri darma perguruan tinggi dan wajib dilaksanakan oleh civitas akademika. Pelatihan ini dilakukan di kampus STMIK PPKIA Pradnya Paramita (STIMATA) Malang. Pelatihan ini dilakukan setelah dosen-dosen STIMATA mendapatkan pelatihan yang sama dari google berupa program “ Indonesia Android Kejar(IAK)”. Pelatihan ini merupakan bentuk study group yang dikolaborasi dengan pengabdian masyarkat untuk dosen-dosen STIMATA. Tujuan dari pelatihan ini adalah untuk memberikan pengetahuan dan wawasan bagi masyarakat, khususnya siswa-siswi SMK Nasional Malang tentang android. Pelatihan ini juga untuk meningkatkan keterampilan bagi siswa-siswi SMK Nasional Malang untuk membuat aplikasi berbasis android. Pelatihan ini dilaksanakan selama dua hari yaitu Senin-Selasa tanggal 29-30 Januari 2018 di Laboratorium Komputer STMIK PPKIA Pradnya Paramita Malang dari pukul 08.00 W1B sampai dengan 16.00 WIB. Pelatihan ini diikuti oleh 29 siswa-siswi SMK Nasional Malang. Pelatihan ini menggunakan dua aplikasi yaitu android studio yang diinstal pada PC komputer untuk membuat programnya dan java untuk mengkompilasi ketika mau dijankan pada handphone android. Pelatihan ini diberikan materi berturut-turut views, views group, membuat project, aplikasi interactif, deffining dan calling methods serta yang terakhir objected oriented program. Setelah semua materi pelatihan diberikan selanjutnya peserta diberikan tugas berupa membuat project applikasi sederhana yang bisa dijalankan di hp android masing-masing. Untuk memberikan penilaian kemampuan ditugaskan membuat project yang lebih komplek dan diberikan waktu satu bulan yang selanjutnya di kirim ke emailnya tutornya. Hasil akhir pelatihan ternyata semua peserta mampu menerima materi dengan baik dan mampu mengejakan tugas sebagai pengganti ujian dengan baik. Dengan demikian pelatihan ini bisa berjalan seperti yang diharapkan.